2021
DOI: 10.1039/d1ta07865h
|View full text |Cite
|
Sign up to set email alerts
|

Positively charged membranes with fine-tuned nanopores for ultrafast and high-precision cation separation

Abstract: There is significant interest in high-performance positively charged membranes that enable the fast and high-precision separation of various cationic substances for purifying water and recovering precious metals. This study demonstrates...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…For the DABIL membrane, the net effect of decreased size exclusion due to the loose and enlarged membrane pore structure is counterbalanced by the enhanced surface charge density due to the dense multication charged groups. Recent studies have revealed that the interactions between the surface QA groups and Cl – ions are stronger than the interactions between the surface carboxyl groups and the Na + ions . Therefore, the Cl – ions experience stronger electrostatic attraction and are permeated faster through the membrane conducing to the observed low rejection of LiCl than NaCl rejection.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For the DABIL membrane, the net effect of decreased size exclusion due to the loose and enlarged membrane pore structure is counterbalanced by the enhanced surface charge density due to the dense multication charged groups. Recent studies have revealed that the interactions between the surface QA groups and Cl – ions are stronger than the interactions between the surface carboxyl groups and the Na + ions . Therefore, the Cl – ions experience stronger electrostatic attraction and are permeated faster through the membrane conducing to the observed low rejection of LiCl than NaCl rejection.…”
Section: Resultsmentioning
confidence: 99%
“…Simulated brine solutions containing a mixture of aqueous LiCl and MgCl 2 solutions with total concentrations ranging from 1 to 10 g L –1 were used to determine the membrane ion selectivity. The LiCl/MgCl 2 selectivity (S Li + /Mg 2+ ) was calculated using the salt concentrations measured from the rejection experiment using eq where C ion,f is the ion concentration in the feed solutions, and C ion,p is the ion concentration in the permeate solutions.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 3 more Smart Citations